Efektivitas Penerapan Model Pembelajaran REACT (Relating, Experiencing, Applying, Cooperating, Transferring) terhadap Kemampuan Pemecahan Masalah Matematika Peserta Didik - Syamsuddin, Nur Syamsi; Rasyid, Muhammad Rusydi; Tayeb, Thamrin; Nur, Fitriani; Baharuddin (Al asma : Journal of Islamic Education, 2024)
Problem solving skills are an important foundation in understanding and applying mathematical concepts effectively. This ability is one of the main keys in developing a deep understanding of mathematical problem solving. This study aims to examine the effectiveness of the application of the REACT (Relating, Experiencing, Applying, Cooperating, and Transferring) learning model on students' mathematics problem solving skills. This quantitative research with a quasi-experiment applies a non-equivalent group design. This study involved students of class VIII MTsN 2 Enrekang. Data in the study were collected through a problem-solving ability-based learning outcomes test. The collected data were analyzed using descriptive and inferential statistics through an independent sample t-test. The results showed that REACT effectively improved students' mathematics problem solving skills in class VIII MTsN 2 Enrekang. Thus, the REACT learning model is feasible to enhance and develop students' mathematics problem solving skills.